AL-RĀZĪ ON THE THEOLOGIANS' MATERIALISM. Issue 1 (March 2023) - Awad, Amal A.
Abstract: Late in his intellectual life, Faḫr al-Dīn al-Rāzī espoused a dualistic position on the nature of the soul, denying that the soul is in any sense a material body. This view, which in broad terms concurs with Avicenna's, sets al-Rāzī in opposition to the theologians' materialistic stance. To make his position clear, in his last work Almaṭālib al-Rāzī sets out a comprehensive case for the theologians' materialism, before critiquing that position. This paper offers a reconstruction of al-Rāzī's arguments for the theologians' materialism, providing an insight into arguments in the philosophy of mind during the Islamic Middle Ages.